Effect of soil properties on plant growth and diversity at various ages of coal mine reclamation in Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yunanto T, Amanah F, Wulansari AR, Wisnu NP. 2021. Effect of soil properties on plant growth and diversity at various ages of coal mine reclamation in Indonesia. Biodiversitas 23: 459-468. Soil is an essential element for plants to grow. Therefore, it is important to understand the influence of soil properties, especially physical and chemical, on plant growth in coal mine reclamation areas. This study aimed to evaluate the growth and diversity of plants at various ages of reclamation and analyze the factors that most influence their growth and diversity. The study analyzed four soil physical properties and eight soil chemical properties. The research was conducted in mine reclamation areas with different ages: 1, 4, 6, 9, and 11-year-old-plantations for vegetation analysis and soil collection. Principal Component Analysis (PCA) analysis was performed using PAST 4.0 statistics program to analyze the data. The results showed that the 9-year-old plantation had the highest mean Shannon Wiener Index (H’= 1.52), mean basal area (35.04 m2/ha), and mean density (469 trees/ha), while the 4-year-old plantation had the highest mean diameter (28.42 cm). The 1-year-old plantation had the highest clay content of 56.28% and the lowest pH of 3.27. The physical properties of the soil affected the growth rate and diversity of the reclamation area more than the chemical properties of the soil. This can be seen from the cumulative proportion of the two PCA values that described the original condition of 71.20% for soil physical properties and 63.10% for soil chemical properties. Based on this study, bulk density affected the diversity while pH impacted other soil chemical properties.
Keywords: Diversity, mine reclamation, plant growth, soil properties